2022
DOI: 10.3390/ma15072359
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetics and Cytotoxic Responses to Titanium Diboride and Zinc Borate Nanoparticles on Cultured Human Primary Alveolar Epithelial Cells

Abstract: Titanium diboride (TiB2) and zinc borate (Zn3BO6) have been utilized in wide spectrum industrial areas because of their favorable properties such as a high melting point, good wear resistance, high hardness and thermal conductivity. On the other hand, the biomedical potentials of TiB2 and Zn3BO6 are still unknown because there is no comprehensive analysis that uncovers their biocompatibility features. Thus, the toxicogenomic properties of TiB2 and Zn3BO6 nanoparticles (NPs) were investigated on human primary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…In this regard, the chemical, physical, and biological features of B provide medicinal chemists a unique chance to research and develop brand new fields of biomedical sciences, especially in drug discovery [23][24][25]. Recent investigations indicated that BCCs could affect the crucial cellular machineries implicating cell survival, tissue regeneration, and immunogenic responses [26]. Although the toxicity potentials by borenium and borinium compounds are not well known, their antibacterial and antiviral properties have been well documented [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the chemical, physical, and biological features of B provide medicinal chemists a unique chance to research and develop brand new fields of biomedical sciences, especially in drug discovery [23][24][25]. Recent investigations indicated that BCCs could affect the crucial cellular machineries implicating cell survival, tissue regeneration, and immunogenic responses [26]. Although the toxicity potentials by borenium and borinium compounds are not well known, their antibacterial and antiviral properties have been well documented [27][28][29].…”
Section: Introductionmentioning
confidence: 99%